Synergistic effects of warming and organic matter enrichment on coastal phosphorus dynamics at high‐nitrogen concentrations - Shuonan Ma; Ying Zeng; Haijun Wang; Jilin Xu; Cheng Luo; Chunpu Zhao; Zhanfeng Liang; Miao Liu; Erik Jeppesen (Limnology and Oceanography, 2026)
Warming and enhanced nutrient and organic matter (OM) pollution are pervasive drivers of global environmental change that may significantly influence the dynamics of coastal sediment phosphorus (P). Traditional studies have predominantly focused on individual environmental stressors. However, the superposition of multiple stressors can trigger additive or synergistic effects, thereby inducing a cascading response of P dynamics and potentially exacerbating the risk of ecosystem collapse. To elucidate the individual and combined impacts of multiple stressors on sediment P dynamics, we performed a 2‐month mesocosm experiment with factorial combinations of three temperature gradients and two sediment types differing in OM content under high nitrogen loading conditions. We found that: (i) warming and OM, each taken individually, increased sediment P release by 39–207% and 45%, respectively, whereas their combined effect collectively amplified P release to 179–440%; (ii) the interactive impacts of these two co‐occurring stressors on sediment P release were synergistic; (iii) these factors, along with their synergistic interactions, had a cascading net facilitation effect on P release; involving increased populations of phosphate‐solubilizing bacteria, up‐regulation of functional genes ( pho D), enhanced alkaline phosphatase activity, and decreased dissolved oxygen concentration. Combined, these factors, as suggested by piecewise structural equation modeling, explain up to 97% of the observed P release. Our findings provide novel insights into the interactive impacts of co‐occurring anthropogenic stressors on coastal P dynamics, highlighting the necessity of considering the synergistic effects of warming and OM pollution on P release in future conservation planning and coastal zone management.